Novel Gross Deletion Mutations in NTRK1 Gene Associated With Congenital Insensitivity to Pain With Anhidrosis - Li, Lulu; Jia, Chao; Tang, Yue; Kong, Yuanyuan; Xia, Yaofang; Ma, Li (Frontiers in Pediatrics, 2021)
Background: Congenital insensitivity to pain with anhidrosis (CIPA) is a rare inherited autosomal recessive disorder characterized by insensitivity to noxious stimuli, anhidrosis, recurrent fever, and intellectual disability. CIPA is mainly caused by mutations in the neurotrophic tyrosine kinase receptor type 1 gene (NTRK1). This study aims to identify pathogenic mutations underlying CIPA in two unrelated Chinese families. Methods: DNA was extracted from blood samples of patients and their available family members and subjected to whole exome sequencing (WES). Real-time PCR (qPCR), Gap-PCR, and Sanger sequencing were applied to verify the identified variants. Result: We found novel compound gross deletion mutations [exon1-6 del (g.1-1258_10169del); exon5-7 del (g.6995_11999del)] of NTRK1 (MIM 191315) gene in family 1 and the compound heterozygous mutations [c.851-33T>A; exon5-7 del (g.6995_11999del)] in family 2. Interestingly, we discovered the intragenic novel gross deletion [exon5-7 del (g.6995_11999del)] mediated by recombination between Alu elements. Conclusions: The present study highlights two rare gross deletion mutations in the NTRK1 gene associated with CIPA in two unrelated Chinese families. The deletion of exon1-6 (g.1-1258_10169del) is thought to be the largest NTRK1 deletion reported to date. Our findings expand the mutation spectrum of NTRK1 mutations in the Chinese and could be useful for prenatal interventions and more precise pharmacological treatments to patients. WES conducted in our study is a convenient and useful tool for clinical diagnosis of CIPA and other associated disorders.